889 Management of Paediatric Appendicitis During the First Wave of COVID-19: Comparison of Our Centre to National Practice. (12th October 2021) - Darbyshire, A; Miles, J; Towers, A; Tan, C; Toh, S
Abstract: Aim: Our hospital took part in a multi-centre prospective cohort study "the CASCADE study" investigating the management and early outcomes of children with appendicitis in the UK and Ireland during the first wave of the COVID-19 pandemic (1). The aim of this study was to compare our local outcomes to those at a national level. Method: This was a prospective cohort study with data collected from 01/04/2020 to 31/05/2020. Primary outcome was treatment strategy for appendicitis. Secondary outcomes were duration of symptoms, ultrasound findings, rate of simple vs perforated appendicitis and complications. Results: Overall, only a minority (2/24 [8%]) were initially treated non-operatively, with both proceeding to appendicectomy due to pain. Remaining children (24/26 [92%]) were primarily treated with appendicectomy. All were performed laparoscopically with no conversions to open. Ultrasound was performed for most children (23/26 [88%]) which accurately identified appendicitis (22/23 [95%]) and negative appendicectomy rate of zero. Rates of complex appendicitis were not higher than expected (10/26 [38%]) but had a longer duration of symptoms (median 66.0h [IQR21.5] vs 30.0h [27.2], p = 0.008) and more complications (4 vs 1). Post-operative length of stay was significantly shorter for simple appendicitis than complicated (median 1.0d [IQR0.0] vs 4.0 [IQR2.8], p = 0.001). Conclusions: Practice in our centre contrasts with the CASCADE study's National findings where 39% were treated non-operatively, only 48% of appendicectomies were performed laparoscopically, only 53% of children had diagnostic imaging and negative appendicectomy rate was 4.5%. Rates of complications for simple and complex appendicitis were similar, but post-operative length of stay shorter in our centre.